Mulling over Manganyi’s mind: Lessons for rethinking black subjectivity in the decolonial moment - Stevens, Garth (PINS-Psychology in Society, 2016)
The publication of Chabani Manganyi’s (2016) intellectual autobiography, Apartheid and the making of a black psychologist, has once more stimulated a critical engagement with his oeuvre. Whilst there are multiple potential readings of this recent work, I am specifically interested in a selective reading of black subjectivity through this text, especially in the context of the decolonial moment that has come to characterise much of our contemporary politics, and in which black subjectivity itself has become a much debated issue.